KAJIAN PERFORMA PERTUMBUHAN DAN KELULUSHIDUPAN LARVA LELE (C. gariepenus) PEMBERIAN PAKAN Tubifex sp. HASIL KULTUR MASSAL MENGGUNAKAN FERMENTASI KOTORAN BURUNG PUYUH, BEKATUL DAN AMPAS TAHU - Vivi Endar Herawati; Johannes Hutabarat (Pena Akuatika Jurnal Ilmiah Perikanan Dan Kelautan, 2017)
The purpose of the research is to study and find performance through the length and weight growth and survival of larvae feeding catfish with Tubifex sp. Mass culture results using fermented manure quail, rice bran and tofu waste. Test animals used were larvae of catfish (C. gariepenus) with a weight of ± 0.6 g / ind. The research method was experimental. The experimental method completely randomized design with 4 treatments, treatment A (100g / L bran; 100 g / L tofu); B (100 g / L quail manure; 50g / L rice bran; 50 g / L tofu waste); C (50 g / L quail manure; 100g / L rice bran; 50 g / L tofu waste) and D (50 g / L quail manure; 50g / L rice bran; 100g / L tofu waste) and 3 replications. Tubifex sp. naturally fed as many as five times a day. The results showed that feeding Tubifex sp. Mass culture results using fermented quail manure, rice bran and tofu waste significant (P <0.05) in length and biomass catfish larvae but not significant (P> 0.05) on the survival of hatched larvae catfish (C. gariepenus). Larvae catfish (C. gariepenus) have a range of 1.88 -3.94 cm and 31.98 g biomass - 45.95 g, and the survival rate ranges between 96% 98%.Based on research, the treatment of larval feeding catfish with Tubifex sp. Mass culture results in the treatment of 100 g / L quail manure; 50g / L of rice bran; 50 g / L tofu waste out best with a length of 3.94 cm, weight 45.95 g biomass and SR 98%Keyword : Tubifex sp. fermentation, catfish larvae, survival, growth, rice bran; tofu waste, quail manure